KADAR KATEKIN DAN AKTIVITAS ANTIOKSIDAN GAMBIR (UNCARIA GAMBIR ROXB.) DI INDONESIA: TINJAUAN LITERATUR 10 TAHUN TERAKHIR (2015-2025) - Ade Teti Vani; Irwan Triansyah; Nadia Purnama Dewi; Dessy Abdullah; Aryaldy Zulkarnaini (Nusantara Hasana Journal, 2026)
Indonesia is the world’s largest producer of gambier (Uncaria gambir Roxb.), which is rich in catechin, a major bioactive compound with strong antioxidant activity. Variations in catechin content and antioxidant activity of Indonesian gambier are influenced by geographical origin, plant characteristics, and processing and extraction methods. This study aims to comprehensively review the catechin content and antioxidant activity of Indonesian gambier based on scientific publications from the last decade (2015–2025). A narrative literature review method was applied by collecting relevant articles from Google Scholar, ScienceDirect, PubMed, and Garuda databases. Selected studies were original research articles reporting quantitative data on catechin levels and/or antioxidant activity of gambier originating from Indonesia. The results indicate that Indonesian gambier, particularly from West Sumatra, exhibits high catechin content and strong antioxidant activity, although considerable variation exists among regions and extraction techniques. Advanced extraction and purification methods, including solvent optimization and ultrasonic-assisted extraction, were shown to enhance catechin concentration and antioxidant capacity. Indonesian gambier has significant potential as a natural antioxidant source, highlighting the need for quality standardization and further development of processing technologies to support value-added utilization and downstream product development.